Analysis of the Intrinsic Elements on Film Train to Busan (2016) - I Gusti Agung Putri Wirastuti; Ni Made Adhyastri Utami; Ni Made Deni Sriningsih (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2026)
The purpose of this study is to analyze the intrinsic elements of the South Korean film Train to Busan, which was directed by Yeon Sang-Ho. The film Train to Busan (2016) is a film that captures the essence of human nature, especially compassion and fear when faced with unexpected and dangerous situations, making it an interesting subject for literary analysis. It tells a story of a father named Seok-woo, who takes his daughter to Busan by train during a sudden zombie outbreak. As the conflict rises, Seok-woo’s character gradually develops into a compassionate, brave and selfless figure. This study uses a qualitative descriptive method to examine the intrinsic elements of the film through observation and interpretation of the themes, characters, characterization, plot, settings, point of view, and the moral value of the film. The analysis reveals that Train to Busan not only presents horror action and survival plot, but it also contains the reflections of social, moral, and emotional struggles in modern society. The result of this study is expected to enrich literary appreciation by showing that a horror survival film can convey deep messages of compassion, sacrifice, and moral strength.